2018
DOI: 10.1109/jphotov.2018.2870532
|View full text |Cite
|
Sign up to set email alerts
|

Review of Statistical and Analytical Degradation Models for Photovoltaic Modules and Systems as Well as Related Improvements

Abstract: In this work, we investigate practical approaches of available degradation models and their usage in photovoltaic (PV) modules and systems. On the one hand, degradation prediction of models is described for the calculation of degradation at system level where the degradation mode is unknown and hence the physics cannot be included by the use of analytical models. Several statistical models are thus described and applied for the calculation of the performance loss using as case study two PV systems, installed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
2
81
0
Order By: Relevance
“…Currently, there are numerous statistical PLR determination methods in the literature to choose from. A comparative study of methods found in the literature has been performed by Lindig et al 1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are numerous statistical PLR determination methods in the literature to choose from. A comparative study of methods found in the literature has been performed by Lindig et al 1 …”
Section: Methodsmentioning
confidence: 99%
“…Several statistical methods have been proposed and compared 1 ; however, there is no industry‐wide consensus, and thus, no standardized approach to PLR calculations. At the IEC level, there was an early effort to introduce a standard or a Technical Reference for the calculation of degradation with the IEC 61724‐Part 4; however, the initial activity was discontinued 2 …”
Section: Introductionmentioning
confidence: 99%
“…[10], three degradation processes are defined and empirically expressed due to the combination of climate degradation factors: Hydrolysis-degradation (k H ) related to the effect of temperature and humidity, photo-degradation (k P ) depends on temperature, humidity and UV irradiance, and thermo-mechanical-degradation (k Tm ) due to high temperature and temperature differences. The models are presented in Equations (11) to (14):…”
Section: Spatial Distribution Of Pv Degradation Ratesmentioning
confidence: 99%
“…For example, while in deserts the risk of sand-storms is high, in highlands wind gusts and snow loads can damage the PV installations. Important findings and calculation methods about the climatic triggers of degradation modes under different climate zones have been presented in [3][4][5][6][7][8][9][10][11]. Irradiation, temperature, and humidity have been identified as the main degradation precursors, leading to different degradation mechanisms depending on the stress level in each climate zone.…”
Section: Introductionmentioning
confidence: 99%
“…STL uses locally weighted regression and thereby provides robust estimates of the trend and seasonal components that are not distorted by outliers and missing values compared to other methods [243,244]. STL handles any type of seasonality, not only monthly or quarterly data.…”
Section: Resultsmentioning
confidence: 99%